(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
In recent decades the practice of architectural drawing has further extended the use – often reckless – of images produced by naively evoke the visual effect of the forms. The widespread distribution of rendering software, in hindsight, has resulted to promote a use of “fake photographs”, rather than by “real drawings”. The figurative techniques that characterized the architectural drawing until the end of the twentieth century, in most cases, were quickly replaced by the results of a figurative culture that is still undeveloped. Despite the success of these images, which can create false illusions about their real ability to communicate, maybe we should – as scholars of representation – to advance openly doubts about their effectiveness. On the other hand, while using very similar computer technologies, in some fields of knowledge in which it is essential that communication through pictures is without any risk of ambiguity – as happens in medicine, life sciences or physics – were explored ways to represent founded on the need to discretize the elements and make them immediately apparent, even at the sacrifice of the yield determined by their visual quality. In a time when the architectural representation is struggling to rebuild its own figurative statute, these images – without being able to be as models – are an example of precision, clarity and effectiveness of communication, similar – in some significant cases – to the outcomes achieved in contemporary painting. Today, in reviewing the tools of architectural drawing, it is more than ever essential to consider the invitation of Klee: «we must make visible and not remake what is already visible».